Optimization of Education System Implementation in Aceh Besar Regency - Putra, I Made Arie Widyasthana Wartana; Luthfi, Ahmad; Amali, Adityal Chisabul; Nurhalisa, Sabrina (Universitas Tribhuwana Tunggadewi, 2024)
In some developed countries, education is one of the main problems in increasing human resource capacity, especially in Indonesia. The principle of decentralization allows the government to create independent laws that give local governments the authority to manage all aspects of education. This study aims to determine the implementation of the education system in Aceh Besar Regency. This study uses a qualitative approach to understand the optimization of the implementation of the education system in Aceh Besar District. Data were collected through interviews, observation, and analysis of data from various literature and previous research. The research findings show that the Aceh Besar District government has taken systematic steps in formulating policies, developing programs, implementing, and monitoring and evaluating education programs. Some of the main programs implemented include the Mobilizer School Program, data-based planning, implementation of the Independent Curriculum, and development of educational facilities and infrastructure. Monitoring and evaluation is carried out through periodic assessments, collecting feedback from stakeholders, and field visits. The evaluation results show an increase in student and teacher performance, as well as the positive impact of the implementation of the policy.AbstrakDi beberapa negara maju pendidikan menjadi salah satu masalah utama dalam meningkatkan kapasitas sumber daya manusia, khususnya di Negara Indonesia. Asas desentralisasi memungkinkan pemerintah untuk membuat undang-undang mandiri yang memberikan wewenang kepada pemerintah daerah untuk mengelola semua aspek pendidikan. Penelitian ini bertujuan untuk mengetahui penyelenggaraan sistem pendidikan di Kabupaten Aceh Besar. Penelitian ini menggunakan pendekatan kualitatif untuk memahami optimalisasi penyelenggaraan sistem pendidikan di Kabupaten Aceh Besar. Data dikumpulkan melalui wawancara, observasi, dan analisis data dari berbagai literatur dan penelitian terdahulu. Temuan penelitian menunjukkan bahwa pemerintah Kabupaten Aceh Besar telah melakukan langkah-langkah sistematis dalam merumuskan kebijakan, menyusun program, mengimplementasikan, serta melakukan monitoring dan evaluasi terhadap program-program pendidikan yang dijalankan. Beberapa program utama yang diimplementasikan antara lain Program Sekolah Penggerak, perencanaan berbasis data, implementasi Kurikulum Merdeka, dan pengembangan sarana dan prasarana pendidikan. Monitoring dan evaluasi dilakukan melalui penilaian berkala, pengumpulan feedback dari stakeholder, dan kunjungan lapangan. Hasil evaluasi menunjukkan peningkatan kinerja siswa dan guru, serta dampak positif dari implementasi kebijakan tersebut.